Use of biological and chemical fungicides and biostimulators for potato protection against early and late blights - Ukolova Anastasiya; Demidova Valentina; Vyatchinov Alexey; Statsyuk Natalia; Kuznetsova Maria (Ratarstvo i Povrtarstvo)
Ecological risks associated with chemical pesticides encourage application of biopesticides and integrated pest management. The study compared efficiency of the Manfil fungicide and Agat-25K biopreparation (single or combined with the ExelGrow biostimulator) against the late (LB) and early (EB) blights of potato. Field experiments were conducted with three potato cultivars (Arizona, Vektor, Aluett) of different resistance levels to the LB and EB diseases. Leaf blight development was registered as LB (Arizona), LB+EB (Vektor), and EB (Aluett). Agat25K delayed LB development under epiphytotic conditions on the susceptible cv. Arizona (biological efficiency 39%), though was inferior to Manfil (62%). On the contrary, for cv. Aluett, Agat-25K showed more significant EB suppression than Manfil (96 vs. 83%). Compared to the control, the yield increase of cv. Arizona was 15.8 t/ha for Agat-25K and 25.4 t/ha for Manfil. Tuber marketability increased by 28 and 13% for Agat-25K and Manfil, respectively. For moderately resistant and resistant cultivars (Vektor, Aluett), Agat-25K provided the highest yield increase compared to Manfil (19.1 vs. 16.7 t/ha for Vektor and 4.5 vs. 1.4 t/ha for Aluett, respectively), while the tuber marketability increased by 15% (Vektor) and 18% (Aluett). Agat-25K can be recommended for use on moderately-resistant cultivars under sporadic LB epiphytoties and for the EB control. ExelGrow application with Manfil and Agat-25K was first shown to improve their biological efficiency on moderately LB-resistant and LB-resistant cultivars (up to 12%).